Influence of shot peening on the microstructure and friction-wear performance of CF53 steel - Qiushen Cai; Huashen Guan; Junjie Zhang; Xiaoguang Zhang; Chenfeng Duan (PLoS ONE, 2025)
In order to further enhance the wear resistance of the camshaft surface, this study conducted shot peening reinforcement on CF53 steel. The research involves the analysis of microstructure, microhardness, and residual stress evolution. Additionally, a pin-on-disk friction and wear test machine was used to investigate the influence of shot peening on the friction-wear characteristics of CF53 steel. The results show that a certain depth of plastic deformation layer is formed on the surface after shot peening, accompanied by an increase in surface roughness. With the increase of shot peening pressure, the surface roughness, microhardness, and residual stress values of the samples correspondingly increase. Shot peening treatment significantly improves the friction-wear performance of CF53 steel, with a reduction of 22.5% and 54.6% in the friction coefficient and wear rate for SP3 and SP4 groups, respectively, compared to untreated samples. The wear mechanism of untreated samples is characterized by severe fatigue wear with prominent features of plowing grooves and cracks. In contrast, the wear mechanism of peened samples shifts to fatigue wear dominated by delamination.